A Pilot Study Delivering Physiotherapy Support for Rett Syndrome Using a Telehealth Framework Suitable for COVID-19 Lockdown. (18th August 2021) - Lotan, Meir; Downs, Jenny; Elefant, Cochavit
ABSTRACT: Background : Rett syndrome (RTT) is a genetically caused neurodevelopmental disorder associated with severe disability. We assessed the feasibility of a telehealth program supporting gross motor skills in RTT. Methods : Five girls with RTT were assessed and a home-based exercise program developed in response to functional goals. Families then participated in monthly Skype sessions for 6 months, guided by a physiotherapist to monitor progress and adjust the program as necessary. Goal Attainment Scaling was used to evaluate progress and a parental satisfaction questionnaire was administered. Results : Four goals were established for each participant and progress was greater than would be expected in 16 of 20 goals. Parents evaluated the program as feasible and useful for their daughters. Discussion : A telehealth model of home-based intervention supported individuals with RTT to achieve gross motor skills and was found to be feasible. This model is important at present times during COVID-19 outbreak and lockdown.